2014
DOI: 10.1039/c4ra05755d
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis of spiro[cyclopropane-1,3′-indolin]-2′-ones through metal-free cyclopropanation using tosylhydrazone salts

Abstract: Anticancer spiro[cyclopropane-1,3′-indolin]-2′-ones are accessible through a transition metal-free diastereoselective cyclopropanation using in situ generated diazo-compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 49 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…On the basis of literature and our outcome, a plausible mechanism was proposed (Scheme ). Initially, aldehyde reacts with TsNHNH 2 and generates corresponding hydrazone intermediate A , which subsequently converts to aryldiazomethane B in the presence of base by the elimination of tosyl group.…”
Section: Results and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the basis of literature and our outcome, a plausible mechanism was proposed (Scheme ). Initially, aldehyde reacts with TsNHNH 2 and generates corresponding hydrazone intermediate A , which subsequently converts to aryldiazomethane B in the presence of base by the elimination of tosyl group.…”
Section: Results and Discussionmentioning
confidence: 86%
“…3-Spirocyclopropyl-2-oxindoles can be traditionally synthesized in a straightforward, diastereoselective manner by treating oxindoles with bromonitroolefins. 7 They can also be obtained by reacting 3-ylidene-oxindoles with 1,2-dihaloalkanes, 8 diazo compounds under the catalysis of dirhodiumtetraacetate, 9 pyridinium salts in the presence of base, 10 ethyl diazoacetate, 11 or bromonitroalkyl derivatives in a Michael–alkylation cascade manner. 12 Alternatively, they can be constructed by the ring contraction of corresponding spiro[pyrazolin-3,3-oxindoles], which are obtained by 1,3-dipolar cycloaddition of 3-ylidene-oxindoles with active diazo partners such as 2,2,2-trifluorodiazoethane, 13 α-diazocarbonyl compounds, 14 or the Bestmann Ohira reagent (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] Maurya et al, reported the metal‐free, diastereoselective cyclopropanation of 3‐alkenyloxindoles by using sodium salt of tosyl hydrazones 38 as a safe alternative of diazo‐compounds (Scheme 11). [ 26 ] BTEAC (benzyl triethyl ammonium chloride) was used to improve the solubility of the reagents ensuring maximum yields of the product. Tosylhydrazone salt 38 at elevated temperature undergoes thermal degradation to produce aryl diazomethane 40 in situ .…”
Section: Synthesis Of Spirocyclopropyl Oxindolesmentioning
confidence: 99%
“…In 2014, Maurya and co‐workers reported a diastereoselective cyclopropanation to construct the spiro[cyclopropane‐1,3′‐indolin]‐2′‐one derivatives 58 using tosylhydrazone salts 57 and 3‐methyleneindolin‐2‐ones 56 (Scheme ) . Mechanistically, this reaction was proposed to proceed via a [3+2] cycloaddition reaction and subsequent loss of nitrogen with the ring contraction sequence.…”
Section: C−c Bond Formationsmentioning
confidence: 99%